Analysis of earthquake precursors in the West Sumatra region based on a magnetic data acquisition system in July 2016-March 2017 - Rahmi Yulyta; Syafriani Syafriani; Ma'muri Ma'muri (Department of Physics – Universitas Negeri Padang UNP, 2017)
Sumatra is one of the most actives seismic islands in Indonesia. West Sumatra as a part of Sumatra, in recent years frequent earthquakes in West Sumatra so many casualties and destroyed thousands of buildings. Until now no one can be sure when the earthquake occurred. Although earthquakes can not be predicted certainty, But the signs of earthquake events can be identified by observation, One of them changes to the earth's magnetic field. Changes in the earth's magnetic field can be identified using the Magnetic Data Acquisition System (MAGDAS). Polarization Power Ratio Z / H is one of the methods used in analyzing changes the variation of earth's magnetic field on component Z and component H. This anomaly change will be adjusted to earthquake occurrence. The results showed that there has been anomalous earth magnetic field 1 day to 1 month before earthquake. Some positive-valued Anomalies indicating rocks experienced strains as of January 11, 2017 corresponding to the earthquake of January 30, 2017 located at -1.87 LU and 98.97 BT with magnitude 4.5 SR, within 19 days after the anomaly. Negative anomalies indicated stress-affected rock as of July 25, 2016 corresponding to the earthquake of August 3, 2016 located at -1.33 LU and 96.86 BT with magnitude 4.7 SR, within 9 days after the anomaly.